2013
DOI: 10.2169/internalmedicine.52.8555
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Oral Tacrolimus in Patients with Moderate/Severe Ulcerative Colitis not Receiving Concomitant Corticosteroid Therapy

Abstract: Objective The calcineurin inhibitor tacrolimus has been shown to be safe and effective as salvage therapy for steroid-refractory ulcerative colitis (UC). Since differences in the onset of action between various agents are thought to influence the achievement and maintenance of disease remission, top-down or accelerated stepup therapy with tacrolimus may be useful. However, the efficacy of tacrolimus in moderate to severe UC patients not receiving concomitant steroids remains unknown. Methods Ten patients (11 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In a prospective multicenter study, we found that rapid induction therapy with oral tacrolimus (started at a dose of 0.1 mg/kg daily without food) achieved a high trough level (10-15 ng/mL) in more than 90% of patients and significantly suppressed the CAI beginning two days after treatment (13). Therefore, the administration of top-down or accelerated step-up therapy with tacrolimus may improve the prognosis of refractory UC, similar to that observed with infliximab in patients with Crohn's disease (6). In Case 1, the patient had steroid-naive UC, and top-down therapy with tacrolimus resulted in a marked improvement.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a prospective multicenter study, we found that rapid induction therapy with oral tacrolimus (started at a dose of 0.1 mg/kg daily without food) achieved a high trough level (10-15 ng/mL) in more than 90% of patients and significantly suppressed the CAI beginning two days after treatment (13). Therefore, the administration of top-down or accelerated step-up therapy with tacrolimus may improve the prognosis of refractory UC, similar to that observed with infliximab in patients with Crohn's disease (6). In Case 1, the patient had steroid-naive UC, and top-down therapy with tacrolimus resulted in a marked improvement.…”
Section: Discussionmentioning
confidence: 71%
“…Since calcineurin inhibitors have a rapid onset of action and are highly effective in patients with refractory UC, they are approved as alternative treatment agents for refractory UC under the national health insurance system in Japan (5). Since differences in the onset of action of various agents are thought to influence the achievement and maintenance of disease remission, early intervention with tacrolimus may improve the long-term prognosis of patients with UC (6). In this paper, we report two cases of severe UC with megacolon that were successfully treated with tacrolimus, including a steroid-naïve patient.…”
Section: Introductionmentioning
confidence: 98%
“…Figure 1 shows the flow diagram which describes the reasons for citations exclusion. Finally, 22 studies (4)(5)(6)(9)(10)(11)(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)28,30,32,33) that fulfilled eligibility criteria were included. Only two studies were randomized controlled trials (24,25) (Ogata 2006 and Ogata 2012); these were included for meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We can obtain more evidence, almost all from retrospective studies, demonstrating relatively good efficacy rates in UC and CD. In UC, retrospective studies have reported remission rates between 9.3-80%, which reflects the high variability between the study population, route of administration, mean drug blood levels and the criteria for evaluating response (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Remission rates demonstrated a similar variability ranging from 9.4-75% in clinical trials and prospective studies (1,2,(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 96%
“…The drug was maintained for a median duration of 11 months (IQR [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Ten patients received the drug for at least 12 months.…”
Section: Treatment Characteristicsmentioning
confidence: 99%